An Overview of Potential Benefits of Ashwagandha (Withania Somnifera) in Prevention and Treatment of Cervical Cancer (International Journal of Ayurveda and Pharma Research, 2025)
Cervical cancer is the fourth most common cancer affecting women worldwide and the second most prevalent among women in India, following breast carcinoma, with an estimated 127,526 new cases annually. Despite advancements in screening and treatment, recurrent and persistent forms of cervical cancer pose a significant therapeutic challenge. Conventional therapies often come with considerable toxicity, limited efficacy in advanced stages, and poor accessibility in low-resource settings. Therefore, there is an urgent need for safer, multi-targeted therapeutic alternatives. In recent years, Ashwagandha is one among the herbal drugs of Ayurveda found useful in different cancers. Ashwagandha leaf is rich in an active principle called withaferin A. Withaferin A (WFA), a steroidal lactone has shown significant anti-neoplastic activity across various cancer cell lines, including cervical cancer, in both in vitro and in vivo models. This paper reviews the anticancer efficacy of Withaferin A in cervical cancer and, for the first time, explores the broader therapeutic potential of Ashwagandha through an integrative perspective. Emphasis is placed on its anti-proliferative, anti-inflammatory, pro-apoptotic, and adaptogenic properties. The potential mechanism of action are also examined through the lens of Panchmahabhautika Sanghatana- the Ayurvedic five-element theory- providing a holistic perspective on Ashwagandha impact on cellular pathology. This integrative approach not only bridges traditional Ayurvedic concepts with contemporary biomedical research but also opens a promising pathway for the development of low-toxicity, plant-based therapies for cervical cancer.